Encephalomyopathies caused by abnormal nuclear-mitochondrial intergenomic cross-talk - Lamperti, C (Pacini Editore SpA, 2009)
Autosomal dominant Progressive External Ophthalmoplegias are Mendelian disorders characterized by the accumulation of multiple deletions of mitochondrial DNA in critical tissues. Most of the Autosomal dominant Progressive External Ophthalmoplegias families carry heterozygous mutations in one of three genes: ANT1, encoding the muscle-heart specific mitochondrial adenine nucleotide translocator, Twinkle, encoding the mitochondrial DNA helicase, and POLG1, encoding the catalytic subunit of the mitochondrial DNA-specific polymerase. Mutations in both POLG1 alleles are also found in autosomal recessive Progressive External Ophthalmoplegias sibships with multiple affected members and in apparently sporadic cases. In addition, recessive POLG1 mutations are responsible for three additional diseases: Alpers-Huttenlocher hepatopathic poliodystrophy, Sensory-Ataxic Neuropathy Dysarthria and Ophthalmoplegia and juvenile SpinoCerebellar Ataxia-Epilepsy syndrome. Mitochondrial neuro-gastro-intestinal encephalomyopathy is an autosomal recessive disorder of juvenile onset, caused by mutations in the gene encoding Thymidine Phosphorylase. Thymidine Phosphorylase is involved in the control and maintenance of the pyrimidine nucleoside pool of the cell. Finally, mitochondrial DNA depletion syndrome is a heterogeneous group of disorders characterized by a reduction in mitochondrial DNA copy number. Clinically, they include a myopathic form, a more generalized encephalomyopathic form and a fatal infantile hepato-cerebral syndrome leading to rapidly progressive liver and brain failure. To date, eight genes have been associated with mitochondrial DNA depletion syndrome. Novel disease genes have recently been added to this list, including OPA1 and GFER, and new clinical variants add further complexity to this expanding area of mitochondrial medicine.